Relationship between serum 25-hydroxyvitamin D concentrations and blood pressure among US adults without a previous diagnosis of hypertension: evidence from NHANES 2005–2018 - Che, Jinhang; Tong, Jin; Kuang, Xue; Zheng, Caiyin; Zhou, Ruoyu; Song, Jiaqi; Zhan, Xiaodan; Liu, Zengzhang (Frontiers in Nutrition, 2023)
Background: There are various cross-sectional studies concluded that vitamin D is associated with blood pressure, but randomized controlled studies have not yielded consistent conclusions. Considering many limitations indeed, our study aimed to examine whether concentrations of 25(OH)D are inversely associated with blood pressure in people without previous diagnosis of hypertension . Method: We analyzed data from the 2005-2018 National Health and Nutrition Examination Survey. Odd ratios (OR) and 95% confidence intervals (CIs) were estimated applying multivariable logistic regression models. The dose-response relationship was assessed by means of restricted cubic spline regression, and stratification analyses were employed to test the consistency between subgroups. Results: Of 17,467 participants aged≥20 years old without previous diagnosis of hypertension , 4,769 had higher blood pressure. Compared to individuals whose 25(OH)D levels were in the bottom quartile (<44.3nnol/L), adjusting for multiple confounders, the ORs for higher blood pressure were 0.90(95%CI 0.78, 1.05), 0.85(95%CI 0.72, 0.99), and 0.86(95%CI 0.72, 1.02), respectively (P for trend =0.096). Furthermore, as a continuous variable, 25(OH)D concentrations were non-linearly associated with an increased risk of hypertension (P < 0.001). The interaction between sleeplessness subgroup and higher blood pressure was significant (P=0.042). Conclusion: In adults without previous diagnosis of hypertension in the United States, concentrations of 25(OH)D were inversely associated with higher blood pressure when it was <84 nmol/L.